Building between Eastern and Western Mediterranean Lands : Construction Processes and Transmission of Knowledge from Late Antiquity to Early Islam - Gilento, Piero, (Arts and Archaeology of the Islamic World ;, 2022)
This edited volume examines the construction processes and the mechanisms of transmission of knowledge between the eastern and western Mediterranean lands from the late Roman period to the early centuries of Islam. The essays explore issues of material culture, craft techniques, technological and typological changes and cultural contacts in Syria, Jordan, North Africa and Spain. The volume includes case studies on prestigious architectural complexes, defensive systems and other structures located in major urban centres (Cyrrhus, Bosra, Jerash, Sousse, Kairouan and Cordoba), as well as minor sites and rural buildings. It offers a fresh contribution to the long-lasting historiographic debate on the transition from antiquity to the Middle Ages and how Early Islamic architecture fostered the structural assumptions for new building experiences in many Mediterranean regions. Contributors: Antonio Almagro, Shaker Al Shbib, Stefano Anastasio, Ignacio Arce, Jean-Claude Bessac, Pascale Clauss-Balty, Piero Gilento, Mattia Guidetti, Pedro Gurriarán Daza, Roberto Parenti, Pauline Piraud-Fournet, María de los Ángeles Utrero Agudo, Jean-Pierre van Staëvel, Apolline Vernet, François Villeneuve.